Resolving the phylogenetic position of Ombrocharis (Lamiaceae), with reference to the molecular phylogeny of tribe Elsholtzieae. Issue 1 (19th February 2016) - Chen, Ya-Ping; Drew, Bryan T.; Li, Bo; Soltis, Douglas E.; Soltis, Pamela S.; Xiang, Chun-Lei
Abstract: Ombrocharis is the only incertae sedis genus within Lamiaceae that has not been included in a published molecular phylogenetic study. Here, we adopt a two‐step approach to resolve the phylogenetic placement of the genus. Initially, the subfamilial affiliation of Ombrocharis was determined based on a combined ndhF and rbcL dataset covering all seven subfamilies of Lamiaceae. Results show that Ombrocharis is a member of Nepetoideae, a placement that is also supported by its hexacolpate pollen grains. In the second set of analyses, two nrDNA (ITS, ETS) and four cpDNA ( ycf1, rps15‐ycf1, trnL‐F, rpl32‐trnL ) markers were used to explore the position of Ombrocharis within Nepetoideae. Our results demonstrate that Ombrocharis and another monotypic genus, Perillula, form a clade that is sister to the remaining genera of tribe Elsholtzieae. Ombrocharis and other taxa within Elsholtzieae share divergent stamens, a weakly 2‐lipped corolla, and an asymmetric disc with an elongate anterior lobe, but it is unclear whether these features are apomorphic. This study represents both the most comprehensive phylogenetic analysis of Elsholtzieae to date and the only study to include all genera of Elsholtzieae. The monophyly of Elsholtzieae (including Ombrocharis ) is well supported, and there is weak support for Elsholtzieae as sister to the rest of Nepetoideae. Additionally, our results do not support the merging of Keiskea with Collinsonia, and Elsholtzia may be polyphyletic.